2008
DOI: 10.1007/s12021-008-9021-2
|View full text |Cite
|
Sign up to set email alerts
|

KInNeSS: A Modular Framework for Computational Neuroscience

Abstract: Making use of very detailed neurophysiological, anatomical, and behavioral data to build biologically-realistic computational models of animal behavior is often a difficult task. Until recently, many software packages have tried to resolve this mismatched granularity with different approaches. This paper presents KInNeSS, the KDE Integrated NeuroSimulation Software environment, as an alternative solution to bridge the gap between data and model behavior. This open source neural simulation software package prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The minimal numbers of compartments and currents needed to produce the desired network properties is used in each neuron's unbranched cable sections (Rall, 1962). The model implements online spike-timing-dependent plasticity (STDP) learning (Gorchetchnikov et al, 2005a), and the plastic synaptic weights, as well as each neuron's compartmental currents, are recorded to allow off-line local-field potentials (LFP), current-source densities (CSD), and oscillation frequency/synchrony analysis (Versace et al, 2007). Stimuli are horizontally or vertically oriented bars that enable testing of model hypotheses about match/mismatch dynamics and learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal numbers of compartments and currents needed to produce the desired network properties is used in each neuron's unbranched cable sections (Rall, 1962). The model implements online spike-timing-dependent plasticity (STDP) learning (Gorchetchnikov et al, 2005a), and the plastic synaptic weights, as well as each neuron's compartmental currents, are recorded to allow off-line local-field potentials (LFP), current-source densities (CSD), and oscillation frequency/synchrony analysis (Versace et al, 2007). Stimuli are horizontally or vertically oriented bars that enable testing of model hypotheses about match/mismatch dynamics and learning.…”
Section: Discussionmentioning
confidence: 99%
“…4.12 Simulation environment. The model is implemented in KInNeSS (KDE Integrated NeuroSimulation Software, www.kinness.net), a software package that allows the simulation of single neurons with multiple compartments as well as large networks of such elements (Versace et al, 2007). All off-line data analysis is implemented in Matlab (Mathworks Inc.).…”
Section: Neurotransmitter Releasementioning
confidence: 99%
“…Mathematical equations and parameters, as well as details pertaining to the simulation protocol, are included in the Appendix. All simulations were conducted using KDE Integrated Neurosimulation software (KInNeSS; Versace et al 2008). …”
Section: Methodsmentioning
confidence: 99%
“…In particular, Tallon et al (1995) reported a 30Hz component over areas covering visual cortices in response to a Kanizsa triangle stimulus. In order to probe the synchronous dynamics of the network measured at a larger scale, cell activity across the 1D array of layer 2/3 cells obtained during simulations of an illusory contour (8 units wide flankers separated by a 5 units wide gap) was combined into a single estimate of the local field potential (LFP) according to the methodology described in Versace et al (2008). The resulting signal was Fourier transformed (FFT) to obtain the power spectrum displayed in Figure 12.…”
Section: Gamma Band Oscillations Synchrony and Perceptual Groupingmentioning
confidence: 99%
See 1 more Smart Citation